Contamination and health risk assessment of lead, arsenic, cadmium, and aluminum from a total diet study of Jilin Province, China. Issue 10 (4th September 2020) - Wang, Bo; Liu, Ya; Wang, Hui; Cui, Lianzhi; Zhang, Zhihao; Guo, Jinzhi; Liu, Sijie; Cui, Weiwei
Abstract: Lead (Pb), arsenic (As), cadmium (Cd) and aluminum (Al) are the four most common heavy metals and can cause serious harm to human health. To evaluate contamination levels and associated safety issues of the four common heavy metals of the residents in Jilin Province, China, a total diet study (TDS) method was used. Concentration and consumption data of the four heavy metals were collected from the fifth Chinese TDS of Jilin province. In total, 12 food groups were studied and two regions were selected for comparison. According to the results, the mean concentration of lead, arsenic, cadmium, and aluminum was 0.0189, 0.0691, 0.0085, and 9.309 mg/kg, respectively. Aluminum in deep‐fried dough sticks exceeded the national limit standard. Pollution of the Songhua River Basin is not very different from that of other areas. The average consumer exposure to the four heavy metals in the 2 to 6‐year‐old group was the highest among all age‐groups. Potatoes and their products were the primary sources of dietary exposure to lead. Aquatic products and their related commodities had the highest contribution to arsenic exposure. Vegetables and vegetable products were the main sources of dietary exposure to cadmium. The highest contributor to aluminum in the diet was from cereals and cereal products. In general, there might be some potential risks to the 2 to 6‐year‐old population due to exposure to lead and aluminum. Contamination of aluminum in cereals and cereal products needs further consideration. Abstract : This study evaluated contamination levels and associated safety issues of four common heavy metals, lead, arsenic, cadmium, and aluminum, using a total diet study of people from Jilin Province, China. The exposures to lead, arsenic, cadmium, and aluminum through the diet are at relatively safe levels; however, there might be some potential risks to the 2‐ to 6‐year‐old population due to exposure to lead and aluminum.